Surgical Masks May Hide Neurological Diagnoses - Martin S. Gizzi; Ryan J. Mason; Andrew Amaranto (Case Reports in Neurology, 2022)
COVID-19 has disrupted the routine flow of patients through emergency departments (EDs) across the globe, including the need to consider COVID-19 for nearly all presenting complaints. The constraints of mask wearing and isolation have created inherent barriers to timely stroke care. We present a case that highlights one of the many ways in which the pandemic has negatively impacted the care of the non-COVID patient. A patient presented to the ED with a chief complaint of diffuse weakness and a new-onset cough on awakening. His daughter noted that he was slurring his words. An emergency medicine resident evaluated him, ordered laboratory studies, and decided to monitor the patient. The same resident later noted the patient veering to the left when walking, prompting a more detailed neurological examination. On removing the patient’s facemask, a left lower facial weakness was evident. The resident called a Code Stroke roughly 50 min after the patient initially presented to the ED. The patient proved to have an acute infarct at the right thalamocapsular junction. Universal masking policies during the COVID-19 pandemic should not prevent the routine assessment of cranial nerve function for all patients presenting to an ED.